2020
DOI: 10.3390/jcm9020547
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Vitamin D Status in Chronic Inflammatory Disorders: How does Chronic Inflammation Affect the Reliability of Vitamin D Metabolites in Patients with IBD?

Abstract: Evidence gained from recent studies has generated increasing interest in the role of vitamin D in extraskeletal functions such as inflammation and immunoregulation. Although vitamin D deficiency has been implicated in the pathophysiology of inflammatory diseases including inflammatory bowel disease (IBD), evidence as to whether vitamin D supplementation may cure or prevent chronic disease is inconsistent. Since 25OH-vitamin D (25OHD) has been suggested to be an acute-phase protein, its utility as a vitamin D s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 53 publications
2
10
0
1
Order By: Relevance
“…In this line, Aksan and colleagues have recently reported a study in which they analysed the serum levels of 25OHD, vitamin-D-binding protein (VDBP), 1,25-dihydroxyvitamin D (1,25OHD) and dihydroxycholecalciferol (24,25OHD) in a cohort of IBD patients and demonstrated that serum total 25OHD was the only vitamin D metabolite without a correlation with the levels of inflammatory parameters. Hence, in this study, authors suggest that total 25OHD seems to be the best marker of vitamin D concentration in IBD patients regardless of the inflammatory status [108]. However, there are still several questions that still need an answer: Is the supplementation of vitamin D beneficial for IBD patients?…”
Section: Food Components and Xenobioticsmentioning
confidence: 73%
“…In this line, Aksan and colleagues have recently reported a study in which they analysed the serum levels of 25OHD, vitamin-D-binding protein (VDBP), 1,25-dihydroxyvitamin D (1,25OHD) and dihydroxycholecalciferol (24,25OHD) in a cohort of IBD patients and demonstrated that serum total 25OHD was the only vitamin D metabolite without a correlation with the levels of inflammatory parameters. Hence, in this study, authors suggest that total 25OHD seems to be the best marker of vitamin D concentration in IBD patients regardless of the inflammatory status [108]. However, there are still several questions that still need an answer: Is the supplementation of vitamin D beneficial for IBD patients?…”
Section: Food Components and Xenobioticsmentioning
confidence: 73%
“…The deficiency was observed in 52% of children with IBD [ 53 ]. A sufficient vitamin D level was found more often in patients with a non-inflammatory disease activity; however, the serum concentration level was not correlated with any inflammatory markers [ 54 ]. In terms of IBD patients, a vitamin D dose of 1820 IU was sufficient to maintain the normal 25(OH)D serum level [ 55 ].…”
Section: The Importance Of Vitamin Intake In Ibd and Bone Mineral mentioning
confidence: 99%
“…Of the four proteins, no notable differences were found in the sham group between baseline and day 5, suggesting the possible relevance of these proteins to the therapeutic process of occipital rTMS. Based on mounting evidence, inflammatory response is considered the common pathway of these four candidate biomarkers (55)(56)(57)(58), and is speculated to be a promising target of multiple non-convulsive neurostimulation interventions, including rTMS (59,60), which might partly account for the differences in protein alterations between rTMS and sham treatment.…”
Section: Discussionmentioning
confidence: 99%